COMMUNITY POLICING IN ENGLAND, WALES, AND EUROPEAN UNION: PAST, PRESENT AND FUTURE - Erkan Pala; Ercan Balcıoğlu (Ankara Avrupa Çalışmaları Dergisi)
Community policing philosophy has become an attractive field within the policing literature, exercised enthusiastically by police forces across England and Wales as a response to police and crime related issues ranging from poor policepublic relations to minor crime and disorder. This paper provides a critical appraisal of community participation and problem solving elements of community policing before moving onto explaining how they have been implemented in England, Wales, and European Union. Finally, this study also highlights that there are stubborn and very serious financial, organisational and cultural challenges regarding the successful application of community policing schemes in England, Wales, and European Union